Birth of the Cool : California Art, Design, and Culture at Midcentury. - Armstrong, Elizabeth; Boyd, Michael; Brouwer, Anna; Colpitt, Frances; Hickey, Dave; Hine, Thomas; Jenkins, Bruce; Smith, Elizabeth A.T.; Trent, Mary; Wild, Lorraine (Newport Beach : Orange County Museum of Art Newport Beach, 2007)
Benjamin, Karl ; Eames, Charles & Ray ; Feitelson, Lorser ; Fischinger, Oskar ; Glarner, Fritz ; Hammersley, Frederick ; Lebrun, Rico ; Lundeberg, Helen ; MacDonald-Wright, Stanton ; McLaughlin, John ; Pardo, Jorge ; Rietveld, Gerrit ; Riley, Bridget ; Rothko, Mark ; Schulman, Julius ; Stella, Frank
Birth of the Cool : California Art, Design, and Culture at Midcentury,Andover, Austin, Newport Beach, Oakland, Addison Gallery of American Art, Phillips Academy Andover, Oakland Museum of California Oakland, Orange County Museum of Art Newport Beach, The Blanton Museum of Art, The University of Texas Austin, 2007-10-07. 2008-02-15, 2008-05-18. 2009-02-27, 2008-01-06. 2008-04-13, 2008-08-17. 2009-05-31
boek
Keywords: California; U.S.A